Kerjasama Pemerintah dan NGO dalam Pengarustamaan Isu dan Praktis Politik Lingkungan melalui Program Switch Asia - Apriyani, Sinta (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
Environmental issues are exacerbated by massive natural exploitation such as degraded agricultural land that creates environmental damage in Indonesia. As a response from the government by collaborating with the public for solutions to this challenge. This research focuses on the NGO WWF Indonesia to see collaboration between the Government and various collaborative activities by looking at aspects of issue and policy orientation. This research uses qualitative methods with a descriptive approach and uses Gaffar's theory which aims to analyze and describe the Relationship between Government and NGOs in the Application of Green Politics. Data collection techniques used in this study are Interview, Observation, documentation and Literature Study. Based on the results of the study showed: First, in the aspect of issue orientation by the Government and WWF Indonesia took a stand and action with the establishment of the Switch Asia local harvest program from the failure of the previous government's policy, namely Food Estate which was felt to be the choice of solution to transform into a wiser food system. Second, in the policy aspect by the Government and WWF Indonesia in determining government policy, workshops were conducted at forums involving stakeholders, academics, government and civil organizations that produced the Indonesian food roadmap 2020-2024. WWF Indonesia plays a role in this collaboration because of their ability to address environmental issues. According to the author, despite acting in the same space, collaboration between the Government and NGOs requires trust between the Government and NGOs.